Appropriately Diverse? The Ontario Science and Technology Curriculum Tested Against the Banks Model - Mujawamariya, Donatille; Hamdan, Amani (Canadian Journal of Education/Revue canadienne de l’éducation, 2014)
The growing diversity of Ontario’s population is increasing pressure on the education system to ensure that all students receive equal opportunities to excel academically and develop personally. Students are more likely to succeed if their own racial, ethnic, and cultural identity is reflected in the classroom. This observation applies no less to science than it does to the humanities and social sciences. While science has a universal quality, flowing from its ability to transcend geographic and cultural frontiers, it is also diverse in origin. Science is a global story of achievement in which nearly every racial, ethnic, and cultural group has played a vital role. This diversity is not adequately appreciated in Ontario, Canada, or the Western world because the default assumption of most Europeans and European descendants is that science is fundamentally Western. Science curricula must therefore direct, convince and equip teachers to rebut this assumption and thereby engage the interest of students of all backgrounds. This paper uses classical content analysis to test the 1998 and 2007 versions of the Ontario science curriculum for Grades 1 to 8 against James Banks’s four approaches for ensuring racial, ethnic and cultural diversity in school programs. Our findings show that neither the 1998 nor the 2007 curricula, despite the latter’s claim to implement the principles of an anti-discriminatory education, challenge the perception of science as fundamentally Western in origin. Keywords: Multiculturalism, science education, anti-discrimination, history of science